Cyclic loading behavior of an innovative semi-rigid connection for engineered bamboo-steel hybrid frames. (July 2019) - Huang, Zirui; Chen, Zhongfan; Huang, Dongsheng; Chui, Ying-Hei
Abstract: This paper presents an innovative semi-rigid connection for bamboo-steel hybrid moment frames that comprise engineered bamboo beams and steel columns. The connection incorporates a steel hinge and two steel brackets to carry shear force and moment at the end of the beam, respectively. The bracket consists of two segments-a joint segment connected to beam and an energy dissipation panel (EDP) connected to a column via a base panel. In this way, the connection not only serves as a frame joint, but also as an energy dissipation device. Cyclic loading tests were carried out on 9 connections with various EDP length-to-thickness ratios to investigate their failure mode and hysteresis behavior. It was found that by proper design, damage of the frame can be restricted to the EDP while other parts of the frame are virtually free of damage. Hysteresis loops for the connection exhibit less pinching than dowel or bolt type connections. The connection has adequate initial stiffness, strength and ductility to meet structural design requirements. A simplified formula to predict the load-carrying capacity of the connection was developed based on the experimental and numerical results. Good agreement was achieved between the results of calculation and experiment. Recommendations are made for the design of the proposed semi-rigid bamboo-steel hybrid connection. Highlights: We innovated a semi-rigid connection for mid- and high-rise bamboo-steel hybrid structures. The connection can be used as not only a moment-frame joint, but also an energy dissipation device. The performances, damage and failure mode of the connection can be well controlled as expected. Formulas for predicting the stiffness and strength of the connection are provided. Suggestions for the design of connection were proposed.